1998
DOI: 10.1039/a806331a
|View full text |Cite
|
Sign up to set email alerts
|

Polymer backbone disassembly: polymerisable templates and vanishing supports in high loading parallel synthesis

Abstract: In the synthesis of a library of N-alkyl-3-aza-8-oxabicyclo[3.2.1]octane-6,7-dimethanol derivatives, prepared from an 7-oxabicyclo[2.2.1]hept-2-ene-5,6-dimethanol derivative via ring opening metathesis polymerisation using Cl 2 (Cy 3 P) 2 RuNCHPh, selective alkylation, ozonolytic scission of the polymer backbone and reductive alkylation, purification was facilitated by the differential solubility of the polymer intermediates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…212 This short summary of what was done or what might be done with cotton as a solid support (but, in general, with any textile-like material) should stimulate the reader's creativity and remove traditional ways of thinking about types and shapes of materials available for the solid-phase synthesis. An ideal solid support would actually disappear at the end of the synthesis (this is not fantasy any moresBall et al 232 have shown that a polymeric support can be created from a monomer, which is actually one of the building blocks in the synthesis, and at the end the total destruction of the polymer leads to the desired compound). Cotton does not disappear, but on the other hand it is so inexpensive, that its persistence is almost unnoticeable.…”
Section: Continuality Of the Cotton Carriermentioning
confidence: 99%
“…212 This short summary of what was done or what might be done with cotton as a solid support (but, in general, with any textile-like material) should stimulate the reader's creativity and remove traditional ways of thinking about types and shapes of materials available for the solid-phase synthesis. An ideal solid support would actually disappear at the end of the synthesis (this is not fantasy any moresBall et al 232 have shown that a polymeric support can be created from a monomer, which is actually one of the building blocks in the synthesis, and at the end the total destruction of the polymer leads to the desired compound). Cotton does not disappear, but on the other hand it is so inexpensive, that its persistence is almost unnoticeable.…”
Section: Continuality Of the Cotton Carriermentioning
confidence: 99%
“…We decided to use norbornyl monomers in these studies for three reasons . First, they polymerize readily by ring-opening metathesis with Grubbs well-defined ruthenium catalysts .…”
mentioning
confidence: 99%
“…With ROMP, the polymer consists solely of repeating monomer units, and as such provides a method for obtaining polymers in which the loading approaches quantitative. We have described the use of such polymers for the preparation of combinatorial libraries by oxidative dissassembly of the polymer backbone and as polymer supported reagents for use in solution phase chemistry …”
mentioning
confidence: 99%